Does Reading Words Differing in Arousal Load Influence Interference Control in Flanker Task? - Imbir, Kamil K. (Curr Psychol, 2015)
Arousal involves a physiological and psychological state of being awake or reactive to stimuli. It could be treated also as an energetic property of stimulation. On the basis of previous findings concerning affective state modulation of spatial processing, I predict that arousal impact will follow the Yerkes-Dodson law. To test this hypothesis, 135 words were chosen and divided into three levels of arousal (low, medium and high), whilst controlling for valence, concreteness, frequency of appearance and length. Forty-nine individuals performed a flanker task while reading the words in order to provide a measure of interference control over spatial processing. The accuracy of answers, reaction times and interference effect index were analyzed. It appears that, at the medium arousal level of words, arousal was optimal for interference control, while both low and high arousal impaired the cognitive control of interference caused by competing flanker and target stimuli features.